Peran Guru Dalam Bermain Permainan Tradisional Egrang Boloak Untuk Meningkatkan Perkembangan Motorik Kasar Pada Anak Usia Dini - Lestri Anggraini; Dwi Nomi Pura; Syisva Nurwita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Gross motor development is a crucial aspect requiring optimal stimulation in early childhood; it encompasses body balance, movement coordination, muscle strength, and self-confidence during physical activities. Preliminary observations at PAUD Aulia Tusyifa (Lubuk Sini Village, Taba Penanjung District, Central Bengkulu Regency) revealed that most children aged 5–6 years exhibited suboptimal gross motor skills, and teachers had not fully utilized traditional games as learning media. This study aimed to describe the teacher's role as a facilitator and motivator during *egrang boloak* (traditional stilts) play activities and to identify the factors supporting or hindering their implementation. A qualitative method with a descriptive approach was employed, involving two teachers and ten children from Group B as research subjects. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles and Huberman model. The results indicated that the teachers performed their roles as facilitators and motivators reasonably well, although there were limitations regarding equipment readiness and motivational approaches that were not yet fully individualized. The *egrang boloak* game proved to have a positive impact on the children's gross motor development: four children showed excellent development, three developed as expected, two were beginning to develop, and one had not yet developed. These findings highlight the need to enhance teacher competence in integrating traditional games as effective educational media within early childhood education institutions.